By Any Means Necessary? When and Why Low Group Identification Paradoxically Predicts Radical Collective Action. (September 2015) - Jiménez‐Moya, Gloria; Spears, Russell; Rodríguez‐Bailón, Rosa; de Lemus, Soledad; Stroebe, Katherine; de Lemus, Soledad
<x xml:space="preserve">Abstract</x> Radical action against social disadvantage is highly consequential but has been far less studied than moderate collective action. But who supports such extreme actions and why? In two studies, we examine the relation between group identification and support for radical action in disadvantaged groups. Paradoxically, low identifiers are more willing than high identifiers to endorse radical action. We argue that high identifiers are more concerned about how radical action could harm their social identity than low identifiers. By contrast, low identifiers are more willing to confront the disadvantage by radical means, adopting a nothing‐to‐lose mindset. Consistent with this, support for radical action was strongest among low identifiers, especially when the in‐group accepted the disadvantage as legitimate (creating a more desperate situation: Studies 1 and 2) and when they were not dependent on the out‐group (and thus had nothing‐to‐lose: Study 2).